Fear without Power: The Awe of the Contemporary Sunni Scholars (haybat al-ʿulamāʾ) - Belhaj, Abdessamad (Interdisciplinary journal for religion and transformation in contemporary society, 2025)
This paper first discusses the idea of haybat al-ʿulamāʾ in Muslim mediaeval resources in order to give a brief but critical background for this concept as it evolved in modern Islamic ethics. I then examine six discourses produced by well-known contemporary salafi (Muḥammad ibn Ṣāliḥ al-ʿUthaymīn, Sayyid Saʿīd ʿAbd al-Ghanī, Saʿd al-Burayk) and Islamist religious scholars (Muḥammad al-Ṣaghīr, ʿAlī al-Ṣallābī, Hāni Muḥammed Yūsuf al-Sibāʿī) in Saudi Arabia, Egypt, and Libya. Finally, I will outline the framework of salafi and Islamist perspectives on how the awe of the religious scholar pertains to his authority. I will also consider the question of how the awe of the scholar either rivals or enhances that of the state (haybat al-dawla).